ANALISIS PENGEMBANGAN AGRIBISNIS TANAMAN NILAM DI KABUPATEN KONAWE - Sukawati, Lukman (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The purpose of this research are: (1) to know the agribusiness of patchouli in Konawe Regency, (2) to know the feasibility of agribusiness of patchouli farmers in Konawe Regency, and (3) to know the pattern of future patchouli agribusiness development (market opportunity and patchouli refining industry) in Konawe District. The results of the research are: (1) Subsystem of supply of production facilities in the development of patchouli agribusiness is one of the supporting factors in increasing income and acceptance level of farmers. The provision of production facilities for patchouli agribusiness is felt to be quite easily accessible for patchouli farmers, especially the availability of fertilizer and medicine (2) the subsystem of farming (production) is a subsystem of farming is activities that used capital goods and natural resources to produced primary agricultural commodities. In supporting the success of farming, it requires the competitiveness of patchouli through the planting of superior seeds and the increasing of patchouli market share. (3) Processing subsystem is the industry that process primary agricultural commodities into processed products both intermediate and final products. Related to this subsystem of patchouli farmers in Anggaberi district generally sells their crops after harvest. After sorting of crops submitted to collecting merchants